EVALUASI KINERJA PILAR JEMBATAN LEMAH IRENG II BERDASARKAN PERFORMANCE BASED SEISMIC DESIGN - Farah Amrina; Muhammad Riyansyah; Aris Aryanto; Erwin Lim (TEKNISIA, 2023)
Lemah Ireng II Bridge is a type of box girder balance cantilever bridge located in Semarang Regency, Central Java, which was completed in 2014. The renewal of bridge loading regulations in 2016 consisted of SNI 1725:2016 for standard load and SNI 2833:2016 for earthquake load. Changes in earthquake loading regulations resulted in an increase in the ground surface spectra value in the short period (Sds, T=0,2 second) in the longitudinal direction by 38.47% and in the transverse direction by 45.39% as a result of updating the earthquake map and the earthquake response modification factor. To determine the level of bridge performance against the applicable earthquake regulations based on the pier structure parameters, the Non-Linear Time History Analysis (NLTHA) method is used. The NLTHA method uses seven deaggregated ground motion records which aim to represent the ground motions that occur at the bridge site. Parameter limits at the pier to determined performance level of bridge based on NCHRP Synthesis 440 and NCHRP Research Report 949. According to the results of performance-based analysis, the bridge pier structure meets the Fully Operational performance level based on the parameters of drift, compressive strain of concrete and tensile strain of steel reinforcement. At this level of performance, after an earthquake the structure suffers very little damage so no repairs are needed and the bridge can function immediately after the earthquake.